Use of applied behavioral techniques and an adaptive device to teach lip closure to severely handicapped children - Petersen, P; Ottenbacher, K (American journal of mental deficiency, 1986)
The effectiveness of applied behavioral programming in teaching lip closure was investigated with 3 severely retarded male students who had oral motor dysfunction. A multiple-baseline design across subjects was employed. The results revealed dramatic increases in the level of functional lip closure for all 3 students when an appropriate adaptive device was combined with behavioral intervention. Follow-up results indicated that functional lip closure generalized to other feeding tasks. Findings suggest that applied behavioral management may be successfully used to teach specific oral motor skills and facilitate integration of these skills into a normalized feeding pattern.